КОМБІНОВАНЕ КЕРУВАННЯ ДВОНАПРАВЛЕНИМИ DC-DC ПЕРЕТВОРЮВАЧАМИ ДЛЯ ВИСОКОДИНАМІЧНИХ НАВАНТАЖЕНЬ - Пересада, С.М.; Ніконенко, Є.О.; Ляшевський, С.Е. (Інститут електродинаміки НАН України, Київ, 2026)
The paper presents design of cascaded DC-link voltage control systems for bidirectional buck-boost DC-DC converters which supply high dynamic loads such as IPMSM electrical drives. A new design methods applied for class of commutated DC-DC converters, which known as strongly nonlinear and non-minimum-phase plants, improved not only their dynamic performance but defined a new system features and therefore new opportunities for their further development and optimization. Control algorithm based on PI current and voltage controllers forms the composite system which consists of two linear stable subsystems in a nonlinear feedback loop suitable to apply the theory of cascaded systems with two time-scale separation of the control loops dynamics. As it follows from the analysis after linearization, the load current acts not only as external disturbance but defines closed loop systems parameters as well, and consequently their dynamics and stability. To overcome this problem the combination of two technologies has been proposed for controller design: a) “symmetrical” like optimum with worst-case system tuning in order to preserve system stability margin depending on maximum values of loads; b) disturbance rejection technique to improve accuracy of voltage regulation on the base of direct load current measurement or estimation. Two technologies do not contradict each other since later one is an intrinsically open loop. When DC-DC converter is used as power supply of vector controlled drives the required load information is computed from the power balance equation of complete electromechanical system ‘DC-DC converter – electrical drive’. The composite electromechanical system ensures high dynamic performance and extended power capability of the DC-DC converter, which is confirmed by the results of experimental tests and simulation study based on experimental transients of the electrical drive. References 13, Fig. 7, Table 1.